Magnetic multi-efficiency polymer inorganic hybrid amphiphilic particle as well as preparation method and application thereof

By using magnetic multi-performance polymer inorganic hybrid gaphene particles, using their multi-layer structure and functional surface team, the problem of difficult to deal with oil-containing wastewater containing partially hydrolyzed polyacrylamide in the prior art is solved, and efficient and repeatable wastewater treatment effect is achieved.

CN119701884AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311262676.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently treat oil-containing wastewater containing partially hydrolyzed polyacrylamide in one step, especially when the pH value of the oil well discharging liquid changes greatly, the treatment is more difficult.

Method used

Magnetic multi-performance polymer inorganic hybrid amphiphilic particles are used, which are coated with a silica/titanium dioxide hybrid shell layer by the core of magnetic Fe3O4 particles, and grafted polydiethylaminoethyl methacrylate (PDEAEMA) and polydopamine on the surface of the shell to form hydrophilic and hydrophobic parts, enhancing the adsorption and migration capture ability of partially hydrolyzed polyacrylamide.

Benefits of technology

The efficient one-step treatment of oil-containing sewage containing partially hydrolyzed polyacrylamide is achieved, which improves the efficiency and effect of sewage treatment, and the particles can be reused, reducing material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004473448330000191
    Figure BDA0004473448330000191
  • Figure BDA0004473448330000201
    Figure BDA0004473448330000201
  • Figure BDA0004473448330000202
    Figure BDA0004473448330000202
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, and provides a magnetic multi-effect polymer inorganic hybrid amphiphilic particle as well as a preparation method and application thereof. The particle comprises a magnetic Fe3O4 particle inner core and a shell layer which is separated from the magnetic Fe3O4 particle inner core in a core-shell manner, and the shell layer is a silicon dioxide / titanium dioxide hybrid shell layer with a fine hole structure; the inner surface of the shell layer and the surface of the magnetic Fe3O4 particle inner core are grafted with poly (diethylaminoethyl methacrylate); the outer surface of the shell layer comprises a hydrophilic part and a hydrophobic part, the hydrophilic part has an amino group, the amino group is grafted with polydopamine, and gallic acid is compounded on the polydopamine. The magnetic multi-efficiency polymer inorganic hybrid amphiphilic particle provided by the invention has excellent emulsifying property, and can realize oil-water separation; meanwhile, partial hydrolyzed polyacrylamide can be selectively adsorbed, and oily sewage containing partial hydrolyzed polyacrylamide can be efficiently treated in one step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment, and more specifically to a magnetic multi-functional polymer inorganic hybrid amphiphilic particle and a preparation method and application thereof. Background Art

[0002] Partially hydrolyzed polyacrylamide (HPAM) is currently widely used in tertiary oil recovery in high-water-content oil fields. It has good flocculation, thickening and drag reduction properties, and can effectively improve the recovery rate. However, the treatment of oily wastewater containing partially hydrolyzed polyacrylamide is more difficult than that of ordinary oily wastewater. Existing methods cannot achieve the standard of partially hydrolyzed polyacrylamide in oily wastewater through one-step treatment. It often requires multiple methods and multiple steps to achieve the standard. In addition, due to differences in oil wells and oil recovery operations, the pH value of the oil well drive fluid varies greatly, and a large amount of wastewater is acidic or alkaline, making it more difficult to treat.

[0003] Amphiphilic solid particle emulsifiers achieve emulsification by reducing the interfacial tension between the two phases, have high interfacial desorption energy, and can achieve efficient and stable emulsification of emulsions; and magnetic amphiphilic solid particles can also make the emulsified droplets magnetic, which is convenient for manipulating the dispersed phase droplets. Therefore, by using magnetic amphiphilic solid particles, stable dispersed phase oil droplets can be obtained by emulsifying the oil phase in water, and then the oil droplets can be migrated and enriched under the control of an external magnetic field, thereby achieving oil-water separation and achieving the effect of treating oily wastewater. However, although the existing magnetic amphiphilic solid particle emulsifier can successfully achieve oil-water separation when used to treat partially hydrolyzed polyacrylamide oily wastewater, it cannot simultaneously and efficiently remove partially hydrolyzed polyacrylamide in one step. Summary of the invention

[0004] The purpose of the present invention is to provide a magnetic multi-functional polymer inorganic hybrid amphiphilic particle and a preparation method thereof, so as to solve the technical problem in the prior art that oily wastewater containing partially hydrolyzed polyacrylamide is difficult to be treated in one step to meet the standards.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a magnetic multifunctional polymer-inorganic hybrid amphiphilic particle, comprising a magnetic Fe 3 O 4 The particle core and the magnetic Fe 3 O 4 The core of the particle is separated into a core-shell layer, wherein the shell layer is a silicon dioxide / titanium dioxide hybrid shell layer with a microporous structure; the inner surface of the shell layer and the magnetic Fe 3 O 4The surface of the particle core is grafted with polydiethylaminoethyl methacrylate (PDEAEMA); the outer surface of the shell layer includes a hydrophilic part and a hydrophobic part, the hydrophilic part has an amino group, the amino group is grafted with polydopamine, and gallic acid is compounded on the polydopamine.

[0007] It should be noted that the "micropore structure" in the present invention includes the intermolecular gaps existing in the silica / titanium dioxide macromolecular skeleton and the silica / titanium dioxide hybrid shell in the presence of the magnetic Fe 3 O 4 Defects generated during the core-shell separation process in the particle core, even micropores and capillaries with a pore size of 0.5 to 50 nm.

[0008] The magnetic multifunctional polymer inorganic hybrid amphiphilic particles provided by the present invention are 3 O 4 The particle core is coated with a layer of silica / titanium dioxide hybrid shell, which can 3 O 4 The core of the particles plays a protective role and can resist the effects of hydrochloric acid, sulfuric acid, nitric acid or various alkaline reagents on the magnetic Fe 3 O 4 The corrosion of the particle core ensures the industrial application of magnetic particles.

[0009] The outer surface of the shell of the magnetic multifunctional polymer inorganic hybrid amphiphilic particles provided by the present invention includes both a hydrophilic part and a hydrophobic part, so that the magnetic multifunctional polymer inorganic hybrid amphiphilic particles have amphiphilicity. Compared with traditional homogeneous particles, they have more stable emulsification properties and can emulsify oil and water phases more stably and more widely to form a stable water-in-oil emulsion, providing a stability basis for the manipulation of emulsion droplets.

[0010] The functional groups on the outer surface of the shell of the magnetic multi-functional polymer-inorganic hybrid amphiphilic particles provided by the present invention have electrostatic and other interactions with partially hydrolyzed polyacrylamide, which promotes the adsorption of partially hydrolyzed polyacrylamide on the outer surface of the shell; and the polydopamine grafted on the amino group of the hydrophilic part and the gallic acid compounded on the polydopamine through strong hydrogen bonding both contain a polyhydroxy structure and have adhesion, which further increases the adhesion and hydrogen bonding of the amphiphilic particles to the partially hydrolyzed polyacrylamide, which is beneficial to improve the effect of the amphiphilic particles in removing partially hydrolyzed polyacrylamide from sewage. At the same time, after achieving the adsorption and adhesion of the partially hydrolyzed polyacrylamide, the internal structural composition of the hybrid amphiphilic particles wetting the partially hydrolyzed polyacrylamide adsorbed on the outer surface of the shell will promote the adsorption process of the partially hydrolyzed polyacrylamide into the shell. The inner surface of the shell and the magnetic Fe 3 O 4The polydiethylaminoethyl methacrylate (PDEAEMA) grafted on the surface of the particle core forms a brush-like coating, which increases the specific surface area and enhances the hydrogen bond density. The microporous structure on the shell provides a channel for the migration and transmission of partially hydrolyzed polyacrylamide, and the weak acidity of partially hydrolyzed polyacrylamide is more conducive to the transfer adsorption of partially hydrolyzed polyacrylamide from the outer surface of the shell to the PDEAEMA inside the shell, thereby achieving the adsorption and migration capture of partially hydrolyzed polyacrylamide by PDEAEMA. The magnetic multi-functional polymer inorganic hybrid amphiphilic particles provided by the present invention greatly improve the adsorption capacity and efficiency of partially hydrolyzed polyacrylamide through the combination of internal and external structures.

[0011] In addition, PDEAEMA is pH-sensitive, showing hydrophilic properties at low pH values ​​and hydrophobic properties at high pH values. This property can be used to achieve repeated adsorption and desorption of partially hydrolyzed polyacrylamide by PDEAEMA, making the magnetic multi-functional polymer-inorganic hybrid amphiphilic particles reusable, greatly reducing the material cost of sewage treatment.

[0012] In addition, the used magnetic multifunctional polymer inorganic hybrid amphiphilic particles can be washed and extracted with a benign solvent of partially hydrolyzed polyacrylamide (such as ethanol), which can also remove the adsorbed partially hydrolyzed polyacrylamide and realize the reuse of the magnetic multifunctional polymer inorganic hybrid amphiphilic particles.

[0013] According to some embodiments of the present invention, the mass ratio of silicon dioxide to titanium dioxide in the shell layer is 1:10 to 10:1.

[0014] According to some embodiments of the present invention, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane.

[0015] The hydrophilic part of the outer surface of the shell is modified with 3-aminopropyltriethoxysilane to have amino groups, which can produce weak interactions with partially hydrolyzed polyacrylamide with carboxyl groups, thereby achieving adsorption of partially hydrolyzed polyacrylamide.

[0016] According to some embodiments of the present invention, the hydrophobic portion is obtained by modifying the outer surface of the shell layer with an alkyl-containing silane coupling agent.

[0017] According to some embodiments of the present invention, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

[0018] According to some embodiments of the present invention, the area of ​​the hydrophilic portion accounts for 1 / 3 to 2 / 3 of the total area of ​​the outer surface of the shell layer.

[0019] According to some embodiments of the present invention, the particle size of the magnetic multifunctional polymer-inorganic hybrid amphiphilic particles is 100 nm<r≤1000 nm.

[0020] In a second aspect, the present invention provides a method for preparing magnetic multifunctional polymer-inorganic hybrid amphiphilic particles, comprising:

[0021] S1. Magnetic Fe 3 O 4 The particles, tetraethyl orthosilicate and tetrabutyl titanate were dispersed in an alcohol solvent to obtain Fe 3 O 4 @SiO 2 / TiO 2 Particles;

[0022] S2. Fe 3 O 4 @SiO 2 / TiO 2 The particles are dispersed in water, paraffin is added, heated until the paraffin is completely melted, stirred and mixed, and filtered after cooling to obtain Fe 3 O 4 @SiO 2 / TiO 2 The particles are embedded in the paraffin surface to form paraffin balls;

[0023] S3. dispersing the paraffin balls into dimethyl sulfoxide, adding an amino-containing silane coupling agent, stirring the reaction, and re-dispersing the obtained solid particles into an alcohol solvent to obtain hydrophilic modified particles;

[0024] S4. The hydrophilic modified particles are dispersed in ethanol, an alkyl-containing silane coupling agent is added, and the reaction is stirred to obtain amphiphilic modified particles;

[0025] S5. The amphiphilic modified particles are mixed with acetic acid for 8-12 hours to obtain core-shell separated amphiphilic modified particles;

[0026] S6. The amphiphilic modified particles separated from the core-shell are dispersed in an alcohol solvent, 4-(chloromethyl)phenyltrimethoxysilane is added for modification reaction; and then grafted with diethylaminoethyl methacrylate to obtain grafted polydiethylaminoethyl methacrylate particles;

[0027] S7. The particles grafted with polydiethylaminoethyl methacrylate are dispersed in a solvent, dopamine is added, and stirred for the first reaction; gallic acid is then added, and stirred for the second reaction. After the reaction is completed, the magnetic multi-functional polymer inorganic hybrid amphiphilic particles are obtained.

[0028] The preparation method of the magnetic multifunctional polymer inorganic hybrid amphiphilic particles provided by the present invention is to use magnetic Fe 3 O 4The particles are used as carriers, and tetraethyl orthosilicate and tetrabutyl titanate are used together in the magnetic Fe 3 O 4 The particle surface is hydrolyzed and the magnetic Fe 3 O 4 The particles are coated to form an effective silicon / titanium-coated iron core-shell structure. Then paraffin with a phase transition temperature of 52°C is used as the oil phase, and Fe 3 O 4 @SiO 2 / TiO 2 The particles act as solid particle emulsifiers and emulsify the oil and water phases at a temperature higher than the phase transition temperature of paraffin to form a stable water-in-paraffin emulsion. After the emulsion is cooled, the paraffin phase solidifies and separates from the water phase to obtain Fe 3 O 4 @SiO 2 / TiO 2 The particles are embedded in the paraffin surface to form paraffin balls, Fe 3 O 4 @SiO 2 / TiO 2 The particles were partially embedded in the paraffin and partially exposed to the paraffin. 3 O 4 @SiO 2 / TiO 2 The outer surface of the particles is modified to be hydrophilic; then the paraffin is removed to expose the Fe 3 O 4 @SiO 2 / TiO 2 The part of the particle that was previously protected by paraffin wax was modified to be hydrophobic, and the amphiphilic particle with both hydrophilic and hydrophobic parts on the particle surface was obtained. Then, the magnetic Fe 3 O 4 The particle size is reduced, the shell layer is separated, and a hollow structure is generated between the core and shell structures. 3 O 4 The particle surface and the inner surface of the shell layer are modified with benzyl chloride [4-(chloromethyl)phenyl]. Benzyl chloride has high activity and can be grafted with polydiethylaminoethyl methacrylate (PDEAEMA) through ATRP (atom transfer radical polymerization). Finally, the particle is reacted with dopamine, polydopamine is grafted on the outer surface of the shell layer, and then gallic acid is compounded on the polydopamine through strong hydrogen bonding to obtain magnetic multi-functional polymer inorganic hybrid amphiphilic particles.

[0029] In the present invention, tetraethyl orthosilicate and tetrabutyl titanate are used in the magnetic Fe 3 O 4The particle surface is hydrolyzed and the magnetic Fe 3 O 4 A dense silica / titanium dioxide hybrid shell structure is formed on the particle surface, which can effectively reduce the magnetic Fe 3 O 4 The particles are protected and can resist the corrosion of hydrochloric acid, sulfuric acid, nitric acid or various alkaline reagents within a certain time and a certain pH range, thereby ensuring the industrial application of the magnetic particles. In addition, the silicon dioxide / titanium dioxide hybrid shell layer in the present invention is a polymer formed by hydrolysis and condensation of tetraethyl orthosilicate and tetrabutyl titanate. Although the formed silicon dioxide / titanium dioxide hybrid shell layer is relatively dense, in the sol-gel process of hydrolysis of tetraethyl orthosilicate and tetrabutyl titanate, the macromolecular skeleton formed by the condensation reaction still has intermolecular spaces, thereby ensuring the smooth progress of the subsequent acid etching treatment, 4-(chloromethyl)phenyltrimethoxysilane modification and PDEAEMA grafting process.

[0030] In the present invention, after acid etching, the magnetic Fe 3 O 4 The particles shrink and core-shell separation occurs. This process will further cause defects in the shell, even micropores or capillaries. The micropore structure composed of the intermolecular gaps in the shell provides a channel for the transmission and migration of partially hydrolyzed polyacrylamide to the interior of the shell.

[0031] In the present invention, the acid etching reagent uses acetic acid, which can make the etching proceed slowly, ensure that the etching process is controllable, and make the magnetic Fe 3 O 4 The surface of the particle core is smoother; if hydrochloric acid, sulfuric acid, etc. are used, it is difficult to control the etching process, which can easily lead to over-etching, making the particle magnetism too weak or even completely disappearing.

[0032] According to some embodiments of the present invention, the alcohol solvent includes at least one of methanol, ethanol, propanol, butanol, isopropanol, and cyclohexanol.

[0033] According to some embodiments of the present invention, the stirring and mixing speed in step S2 is 1000-5000 rpm.

[0034] In the present invention, the stirring speed in step S2 directly affects the particle emulsifier (Fe 3 O 4 @SiO 2 / TiO 2The emulsification process of the particles directly leads to the stabilization of the emulsion interface by the particle emulsifier. When the stirring speed is less than 1000rpm, the stirring speed is too low, the particle emulsifier is difficult to deliver to the interface, the interface cannot be stabilized, and the emulsion is easily broken; when the stirring speed is greater than 5000rpm, the stirring speed is too high, and the particle emulsifier is forced to be pulled at the interface, which easily leads to interface instability and emulsion breaking. Therefore, in order to ensure emulsification and interface stability, it is advisable that the stirring speed in step S2 is controlled at 1000-5000rpm.

[0035] According to some embodiments of the present invention, the stirring and mixing time in step S2 is 3 to 5 minutes.

[0036] According to some embodiments of the present invention, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane.

[0037] 3-Aminopropyltriethoxysilane was used to 3 O 4 @SiO 2 / TiO 2 The local hydrophilic modification of the particle surface was carried out in dimethyl sulfoxide, which was achieved by a hydrolysis process on the Fe2+ exposed to the paraffin wax. 3 O 4 @SiO 2 / TiO 2 The sol-gel composite on the outer surface of the particles 3 O 4 @SiO 2 / TiO 2 One side of the outer surface of the particle is modified with amino groups to achieve the adsorption of partially hydrolyzed polyacrylamide.

[0038] According to some embodiments of the present invention, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

[0039] The Fe 3 O 4 @SiO 2 / TiO 2 The local hydrophobic modification of the particle surface is to first remove the paraffin with an alcohol solvent to make Fe 3 O 4 @SiO 2 / TiO 2 The particles were embedded in paraffin and the protected part was exposed, and then Fe 3 O 4 @SiO 2 / TiO 2 The exposed part of the particles from the paraffin wax was hydrolyzed by n-octyltriethoxysilane to achieve sol-gel composite on the surface.3 O 4 @SiO 2 / TiO 2 The other side of the outer surface of the particle is modified with n-octyl groups.

[0040] According to some embodiments of the present invention, the magnetic Fe 3 O 4 The mass ratio of particles, tetraethyl orthosilicate and tetrabutyl titanate is 1:(0.1-1):(0.1-1).

[0041] According to some embodiments of the present invention, the magnetic Fe 3 O 4 The mass ratio of particles to paraffin is 1:(10-200).

[0042] According to some embodiments of the present invention, the mass ratio of paraffin wax to water is 1:(2-10).

[0043] According to some embodiments of the present invention, the magnetic Fe 3 O 4 The mass ratio of the particles to the amino-containing silane coupling agent is 1:(0.001-0.01).

[0044] According to some embodiments of the present invention, the magnetic Fe 3 O 4 The mass ratio of the particles to the alkyl-containing silane coupling agent is 1:(0.001-0.01).

[0045] According to some embodiments of the present invention, the magnetic Fe 3 O 4 The mass ratio of the particles to 4-(chloromethyl)phenyltrimethoxysilane is 1:(0.001-0.01).

[0046] According to some embodiments of the present invention, the magnetic Fe 3 O 4 The mass ratio of the particles to diethylaminoethyl methacrylate is 1:(0.02-0.1).

[0047] According to some embodiments of the present invention, the magnetic Fe 3 O 4 The mass ratio of particles to dopamine is 1:(0.001-0.01).

[0048] According to some embodiments of the present invention, the magnetic Fe 3 O 4 The mass ratio of the particles to gallic acid is 1:(0.001-0.01).

[0049] According to some embodiments of the present invention, the magnetic Fe3 O 4 The particle size of the particles is 100 to 500 nm.

[0050] According to some embodiments of the present invention, the magnetic Fe 3 O 4 Granular and magnetic Fe 3 O 4 The particle size ratio of the particle inner core is 100:(10~99).

[0051] In the present invention, if the magnetic Fe 3 O 4 Particles and magnetic Fe 3 O 4 The particle size ratio of the core of the particle is less than 100:99, indicating that the shell and magnetic Fe 3 O 4 If the voids in the particle core are too small, the adsorption capacity of the magnetic multifunctional polymer inorganic hybrid amphiphilic particles to partially hydrolyzed polyacrylamide will be affected; if the magnetic Fe 3 O 4 Particles and magnetic Fe 3 O 4 The particle size ratio of the particle core is greater than 100:10, indicating that the magnetic Fe 3 O 4 If the particle core size is too small, it will lead to severe magnetic attenuation, making it difficult to achieve magnetic manipulation of the external magnetic field.

[0052] According to some embodiments of the present invention, the grafting reaction includes: dissolving cuprous chloride and 2,2-bipyridine in a solvent, adding amphiphilic modified particles treated by the modification reaction and diethylaminoethyl methacrylate, and stirring the reaction in a nitrogen atmosphere at 60-100°C.

[0053] According to some embodiments of the present invention, the solvent used in the grafting reaction includes at least one of water, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).

[0054] According to some embodiments of the present invention, the solvent used to disperse the particles grafted with polydiethylaminoethyl methacrylate includes at least one of water, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).

[0055] According to some embodiments of the present invention, the stirring reaction time in step S3 is 5 to 6 hours.

[0056] According to some embodiments of the present invention, the stirring reaction time in step S4 is 5 to 6 hours.

[0057] According to some embodiments of the present invention, the magnetic Fe 3 O4 The particles and tetra-n-butyl titanate are dispersed in an alcohol solvent by ultrasonic and stirring for 12 to 24 hours. Preferably, the ultrasonic frequency is 60 to 80 Hz and / or the stirring speed is 50 to 100 rpm.

[0058] According to some embodiments of the present invention, the Fe 3 O 4 @SiO 2 / TiO 2 The particles are dispersed in water by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 50-100 rpm.

[0059] According to some embodiments of the present invention, the paraffin balls are dispersed in dimethyl sulfoxide by stirring, and preferably, the stirring speed is 50 to 100 rpm;

[0060] According to some embodiments of the present invention, the hydrophilic modified particles are dispersed in the alcohol solvent by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 200-300 rpm.

[0061] According to some embodiments of the present invention, mixing the amphiphilic modified particles with acetic acid for 8-12 hours comprises: dispersing the amphiphilic modified particles in water, adding acetic acid, and mixing for 8-12 hours by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 50-100 rpm.

[0062] In a third aspect, the present invention provides a magnetic multifunctional polymer-inorganic hybrid amphiphilic particle prepared by the preparation method described in the second aspect.

[0063] In a fourth aspect, the present invention provides the use of the magnetic multifunctional polymer-inorganic hybrid amphiphilic particles described in the first aspect or the magnetic multifunctional polymer-inorganic hybrid amphiphilic particles described in the third aspect in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

[0064] The beneficial effects of the present invention are at least:

[0065] (1) The magnetic multifunctional polymer inorganic hybrid amphiphilic particles provided by the present invention have uniform particle size and a wide size distribution window, and can achieve submicron / micron distribution.

[0066] (2) The magnetic multifunctional polymer-inorganic hybrid amphiphilic particles provided by the present invention have excellent emulsification properties. The droplets stabilized by the magnetic multifunctional polymer-inorganic hybrid amphiphilic particles can be controlled by an external magnetic field to achieve the enrichment and migration of oil droplets, thereby achieving oil-water separation.

[0067] (3) The magnetic multifunctional polymer-inorganic hybrid amphiphilic particles provided by the present invention can efficiently treat oily wastewater containing partially hydrolyzed polyacrylamide in one step through the combination of internal and external structures of the particles.

[0068] (4) The magnetic multifunctional polymer-inorganic hybrid amphiphilic particles provided by the present invention can be reused multiple times, and the adsorption capacity for partially hydrolyzed polyacrylamide will not decrease significantly, which can greatly reduce the material cost of sewage treatment.

[0069] (5) The magnetic multifunctional polymer inorganic hybrid amphiphilic particles provided by the present invention have a silica / titanium dioxide hybrid shell layer coated with magnetic Fe 3 O 4 The structure of the particle core can protect the magnetic Fe 3 O 4 The role of the particle core is to improve the acid and alkali resistance of the hybrid amphiphilic particles, so that they can be used to treat sewage with more complex composition.

[0070] (6) The preparation method of the magnetic multifunctional polymer inorganic hybrid amphiphilic particles provided by the present invention has a simple process, low cost and readily available raw materials, and can achieve industrial mass production at the ton level. DETAILED DESCRIPTION

[0071] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0072] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0073] Example 1

[0074] S1. 2g of magnetic Fe 3 O 4 The particles (particle size of 0.2 μm) were dispersed in 200 mL of ethanol, and 1 g of tetraethyl orthosilicate and 1 g of tetrabutyl titanate were added at the same time. Ultrasonication at 60 Hz and overhead stirring at 100 rpm were applied to promote the magnetic Fe 3 O 4 The particles were dispersed for 12 h and Fe3 O 4 @SiO 2 / TiO 2 Particles.

[0075] S2. Fe 3 O 4 @SiO 2 / TiO 2 The particles were dispersed into 200 mL of water, and ultrasound at 60 Hz and overhead stirring at 100 rpm were applied. The ultrasound and stirring were maintained to promote the Fe 3 O 4 @SiO 2 / TiO 2 Dispersion of particles. Raise the water temperature to 80°C, add 20g paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 2000rpm, and continue stirring for 3min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Spread the paraffin balls on filter paper and dry them naturally to obtain Fe 3 O 4 @SiO 2 / TiO 2 Paraffin ball powder formed by particles embedded in the surface of paraffin.

[0076] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 50 rpm. Add 20 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 h. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles.

[0077] S4. Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 The particles were dispersed in 100 mL of ethanol and stirred with an overhead stirrer at 300 rpm with 60 Hz ultrasound. 20 mg of n-octylpropyltriethoxysilane was added to the dispersion and stirred for 6 h. The solid particles were separated by an external magnetic field and dried in a natural state to obtain

[0078] C 8 -Fe3 O 4 @SiO 2 / TiO 2 -NH 2 Particles.

[0079] S5. C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 The particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm and 60 Hz ultrasound to obtain C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles;

[0080] S6. Separation of core and shell C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 The particles were dispersed in 100 mL of ethanol, 10 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and stirred at 100 rpm for 12 h to obtain the modified C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles; 0.02g of cuprous chloride and 0.02g of 2,2-bipyridine were dissolved in 50mL of DMF, and the modified C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 granules, and 0.1 g of DEAEMA was added, and N 2 Deoxygenate for 30 min, heat to 80°C, and stir at 100 rpm for 3 h to obtain particles grafted with poly(diethylaminoethyl methacrylate);

[0081] S7. The grafted poly(diethylaminoethyl methacrylate) particles are dispersed in a solvent, 20 mg of dopamine is added, and the reaction is stirred for 6 hours. Then 20 mg of gallic acid is added, and the reaction is stirred for 6 hours. After the reaction is completed, magnetic multi-functional polymer-inorganic hybrid amphiphilic particles are obtained.

[0082] Example 2

[0083] S1. 2g of magnetic Fe 3 O 4 The particles (particle size of 0.2 μm) were dispersed in 200 mL of ethanol, and 0.3 g of tetraethyl orthosilicate and 0.3 g of tetrabutyl titanate were added at the same time. Ultrasonication at 60 Hz and overhead stirring at 100 rpm were applied to promote the magnetic Fe 3 O 4 The particles were dispersed for 12 h and Fe 3 O 4 @SiO 2 / TiO 2 Particles.

[0084] S2. Fe 3 O 4 @SiO 2 / TiO 2 The particles were dispersed into 200 mL of water, and ultrasound at 60 Hz and overhead stirring at 100 rpm were applied. The ultrasound and stirring were maintained to promote the Fe 3 O 4 @SiO 2 / TiO 2 Dispersion of particles. Raise the water temperature to 80°C, add 40g paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 1000rpm, and continue stirring for 5 minutes. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Spread the paraffin balls on filter paper and dry them naturally to obtain Fe 3 O 4 @SiO 2 / TiO 2 Paraffin ball powder formed by particles embedded in the surface of paraffin.

[0085] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 50 rpm. Add 3 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 h. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles.

[0086] S4. Fe3 O 4 @SiO 2 / TiO 2 -NH 2 The particles were dispersed in 100 mL of ethanol and stirred with an overhead stirrer at 300 rpm with 60 Hz ultrasound. 3 mg of n-octylpropyltriethoxysilane was added to the dispersion and stirred for 6 h. The solid particles were separated using an external magnetic field and dried in a natural state to obtain

[0087] C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles.

[0088] S5. C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 The particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm and 60 Hz ultrasound to obtain C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles;

[0089] S6. Separation of core and shell C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 The particles were dispersed in 100 mL of ethanol, 3 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and stirred at 100 rpm for 12 h to obtain the modified C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles; 0.02g of cuprous chloride and 0.02g of 2,2-bipyridine were dissolved in 50mL of DMF, and the modified C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH2 granules, and 0.04 g of DEAEMA was added, and N 2 Deoxygenate for 30 min, heat to 80°C, and stir at 100 rpm for 3 h to obtain particles grafted with poly(diethylaminoethyl methacrylate);

[0090] S7. The grafted poly(diethylaminoethyl methacrylate) particles are dispersed in a solvent, 3 mg of dopamine is added, and the reaction is stirred for 6 hours. Then 3 mg of gallic acid is added, and the reaction is stirred for 6 hours. After the reaction is completed, magnetic multi-functional polymer-inorganic hybrid amphiphilic particles are obtained.

[0091] Example 3

[0092] S1. 2g of magnetic Fe 3 O 4 The particles (particle size of 0.2 μm) were dispersed in 200 mL of ethanol, and 2 g of tetraethyl orthosilicate and 2 g of tetrabutyl titanate were added at the same time. Ultrasonication at 60 Hz and overhead stirring at 100 rpm were applied to promote the magnetic Fe 3 O 4 The particles were dispersed for 12 h and Fe 3 O 4 @SiO 2 / TiO 2 Particles.

[0093] S2. Fe 3 O 4 @SiO 2 / TiO 2 The particles were dispersed into 200 mL of water, and ultrasound at 60 Hz and overhead stirring at 100 rpm were applied. The ultrasound and stirring were maintained to promote the Fe 3 O 4 @SiO 2 / TiO 2 Dispersion of particles. Raise the water temperature to 80°C, add 20g paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 5000rpm, and continue stirring for 4 minutes. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Spread the paraffin balls on filter paper and dry them naturally to obtain Fe 3 O 4 @SiO 2 / TiO 2 Paraffin ball powder formed by particles embedded in the surface of paraffin.

[0094] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 50 rpm. Add 10 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 h. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles.

[0095] S4. Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 The particles were dispersed in 100 mL of ethanol and stirred with an overhead stirrer at 300 rpm with 60 Hz ultrasound. 10 mg of n-octylpropyltriethoxysilane was added to the dispersion and stirred for 6 h. The solid particles were separated using an external magnetic field and dried in a natural state to obtain

[0096] C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles.

[0097] S5. C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 The particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm and 60 Hz ultrasound to obtain C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles;

[0098] S6. Separation of core and shell C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2The particles were dispersed in 100 mL of ethanol, 15 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and stirred at 100 rpm for 12 h to obtain the modified C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles; 0.02g of cuprous chloride and 0.02g of 2,2-bipyridine were dissolved in 50mL of DMF, and the modified C 8 -Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 granules, and 0.2 g of DEAEMA was added, and N 2 Deoxygenate for 30 min, heat to 80°C, and stir at 100 rpm for 3 h to obtain particles grafted with poly(diethylaminoethyl methacrylate);

[0099] S7. The grafted poly(diethylaminoethyl methacrylate) particles are dispersed in a solvent, 10 mg of dopamine is added, and the reaction is stirred for 6 hours. Then 10 mg of gallic acid is added, and the reaction is stirred for 6 hours. After the reaction is completed, magnetic multi-functional polymer-inorganic hybrid amphiphilic particles are obtained.

[0100] Example 4

[0101] S1. 2g of magnetic Fe 3 O 4 The particles (particle size of 0.2 μm) were dispersed in 200 mL of ethanol, and 1 g of tetraethyl orthosilicate and 1 g of tetrabutyl titanate were added at the same time. Ultrasonication at 60 Hz and overhead stirring at 100 rpm were applied to promote the magnetic Fe 3 O 4 The particles were dispersed for 12 h and Fe 3 O 4 @SiO 2 / TiO 2 Particles.

[0102] S2. Fe 3 O 4 @SiO 2 / TiO 2 The particles were dispersed into 200 mL of water, and ultrasound at 60 Hz and overhead stirring at 100 rpm were applied. The ultrasound and stirring were maintained to promote the Fe 3 O 4 @SiO 2 / TiO 2Dispersion of particles. Raise the water temperature to 80°C, add 20g paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off ultrasound and increase the stirring speed to 500rpm.

[0103] Since the stirring speed is too low, the particles cannot be delivered to the oil-water interface by mechanical force, the silicon / titanium-coated iron magnetic particles cannot be stabilized at the oil-water interface, the oil-water two phases cannot be stably emulsified, the water phase and the oil phase remain two phases, and the paraffin ball powder formed by the silicon / titanium-coated iron magnetic particles embedded in the paraffin surface cannot be obtained.

[0104] Example 5

[0105] S1. 2g of magnetic Fe 3 O 4 The particles (particle size of 0.2 μm) were dispersed in 200 mL of ethanol, and 1 g of tetraethyl orthosilicate and 1 g of tetrabutyl titanate were added at the same time. Ultrasonication at 60 Hz and overhead stirring at 100 rpm were applied to promote the magnetic Fe 3 O 4 The particles were dispersed for 12 h and Fe 3 O 4 @SiO 2 / TiO 2 Particles.

[0106] S2. Fe 3 O 4 @SiO 2 / TiO 2 The particles were dispersed into 200 mL of water, and ultrasound at 60 Hz and overhead stirring at 100 rpm were applied. The ultrasound and stirring were maintained to promote the Fe 3 O 4 @SiO 2 / TiO 2 Dispersion of particles. Raise the water temperature to 80°C, add 20g paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off ultrasound and increase the stirring speed to 6000rpm.

[0107] Due to the high stirring speed, although the silicon / titanium-coated iron magnetic particles were delivered to the oil-water interface by mechanical force to achieve emulsification, the too-fast mechanical stirring caused the particles to peel off at the interface, making the interface unstable and causing emulsion demulsification. It was impossible to produce the paraffin ball powder formed by the silicon / titanium-coated iron magnetic particles embedded in the paraffin surface.

[0108] Comparative Example 1

[0109] S1. 2g of magnetic Fe 3 O 4The particles (particle size of 0.2 μm) were dispersed in 200 mL of ethanol, and 1 g of tetraethyl orthosilicate and 1 g of tetrabutyl titanate were added at the same time. Ultrasonication at 60 Hz and overhead stirring at 100 rpm were applied to promote the magnetic Fe 3 O 4 The particles were dispersed for 12 h and Fe 3 O 4 @SiO 2 / TiO 2 Particles.

[0110] S2. Fe 3 O 4 @SiO 2 / TiO 2 The particles were dispersed into 200 mL of water, and ultrasound at 60 Hz and overhead stirring at 100 rpm were applied. The ultrasound and stirring were maintained to promote the Fe 3 O 4 @SiO 2 / TiO 2 Dispersion of particles. Raise the water temperature to 80°C, add 20g paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 2000rpm, and continue stirring for 3min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Spread the paraffin balls on filter paper and dry them naturally to obtain Fe 3 O 4 @SiO 2 / TiO 2 Paraffin ball powder formed by particles embedded in the surface of paraffin.

[0111] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 50 rpm. Add 20 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 h. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe 3 O 4 @SiO 2 / TiO 2 -NH 2 Particles.

[0112] S4. Fe 3 O 4 @SiO 2 / TiO 2 -NH 2The particles were dispersed in 100 mL of ethanol and stirred with an overhead stirrer at 300 rpm with 60 Hz ultrasound. 20 mg of n-octylpropyltriethoxysilane was added to the dispersion and stirred for 6 h. The solid particles were separated using an external magnetic field to obtain C 8 -Fe 3 O 4 @SiO 2 -NH 2 Particles;

[0113] S5. C 8 -Fe 3 O 4 @SiO 2 -NH 2 The particles were dispersed in a solvent, 20 mg of dopamine was added, and the mixture was stirred and reacted for 6 h. Then, 20 mg of gallic acid was added, and the mixture was stirred and reacted for 6 h to obtain particles.

[0114] Comparative Example 2

[0115] S1. 2g of magnetic Fe 3 O 4 The particles (particle size of 0.2 μm) were dispersed in 200 mL of ethanol, and 1 g of tetraethyl orthosilicate and 1 g of tetrabutyl titanate were added at the same time. Ultrasonication at 60 Hz and overhead stirring at 100 rpm were applied to promote the magnetic Fe 3 O 4 The particles were dispersed for 12 h and Fe 3 O 4 @SiO 2 / TiO 2 Particles.

[0116] S2. Fe 3 O 4 @SiO 2 / TiO 2 The particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h with an overhead stirrer at 100 rpm and 60 Hz ultrasound to obtain core-shell separated Fe 3 O 4 @SiO 2 / TiO 2 Particles;

[0117] S3. Separation of core-shell Fe 3 O 4 @SiO 2 / TiO 2The particles were dispersed in 100 mL of ethanol, 10 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 100 rpm for 12 h to obtain the modified Fe 3 O 4 @SiO 2 / TiO 2 Particles; 0.02g of cuprous chloride and 0.02g of 2,2-bipyridine were dissolved in 50mL of DMF, and the modified Fe 3 O 4 @SiO 2 / TiO 2 granules, and 0.1 g of DEAEMA was added, and N 2 Deoxygenate for 30 min, heat to 80°C, stir at 100 rpm for 3 h, and obtain particles after the reaction is completed.

[0118] Comparative Example 3

[0119] The particles were prepared by referring to the preparation method of Example 1, except that the acetic acid was replaced by an equal volume of dilute hydrochloric acid (pH 6).

[0120] Comparative Example 4

[0121] The particles were prepared by referring to the preparation method of Example 1, except that acetic acid was replaced by an equal volume of sulfuric acid.

[0122] Performance Evaluation

[0123] (I) The particle size of the particles of each embodiment and comparative example was measured using a scanning electron microscope, and the results are shown in the following table:

[0124] Group Particle size (nm) Example 1 320 Example 2 224 Example 3 320 Comparative Example 1 320 Comparative Example 2 240 Comparative Example 3 320 Comparative Example 4 320

[0125] (II) Wastewater treatment effect

[0126] 1 kg of the particles prepared in each embodiment and comparative example were added to 10 t of partially hydrolyzed polyacrylamide oily wastewater (COD value was 2020, petroleum pollutant content was 52.3 mg / L, and partially hydrolyzed polyacrylamide content was 103.05 mg / L), and the oily wastewater was emulsified by stirring at a speed of 1000 rpm for 1 min using a shearing machine; then the migration and enrichment of the emulsified oil droplets of the magnetic particles were achieved by controlling the external magnetic field. The treated wastewater was tested, and the test method is shown in the following table:

[0127]

[0128]

[0129] The test results are shown in the following table:

[0130]

[0131] (III) Cyclic performance

[0132] The magnetic multifunctional polymer inorganic hybrid amphiphilic particles are washed and regenerated by a solvent method, thereby realizing the recycling of the magnetic multifunctional polymer inorganic hybrid amphiphilic particles. The specific treatment method includes: collecting the magnetic multifunctional polymer inorganic hybrid amphiphilic particles prepared in Example 1 after wastewater treatment, washing with ethanol, the mass ratio of ethanol to amphiphilic particles is 10:1, and then freeze-drying after washing to obtain regenerated particles.

[0133] The regenerated particles were used to repeat the treatment process of partially hydrolyzed polyacrylamide-containing oily wastewater in step (ii), and the indicators of the treated wastewater were similar to the treatment effect of the first wastewater treatment using the magnetic multi-functional polymer-inorganic hybrid amphiphilic particles in Example 1. The magnetic multi-functional polymer-inorganic hybrid amphiphilic particles can be recycled for more than 100 times, and the removal effect of COD, petroleum and partially hydrolyzed polyacrylamide will not be significantly deteriorated.

[0134] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A magnetic multifunctional polymer-inorganic hybrid amphiphilic particle, characterized in that: The magnetic multi-functional polymer inorganic hybrid amphiphilic particles include a magnetic Fe3O4 particle core and a shell separated from the magnetic Fe3O4 particle core, wherein the shell is a silica / titanium dioxide hybrid shell with a microporous structure; polydiethylaminoethyl methacrylate is grafted on the inner surface of the shell and the surface of the magnetic Fe3O4 particle core; the outer surface of the shell includes a hydrophilic part and a hydrophobic part, wherein the hydrophilic part has an amino group, the amino group is grafted with polydopamine, and gallic acid is compounded on the polydopamine.

2. The magnetic multifunctional polymer-inorganic hybrid amphiphilic particles according to claim 1, characterized in that: The amino groups on the hydrophilic part are obtained by modifying the outer surface of the shell layer with an amino-containing silane coupling agent; preferably, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane; And / or, the hydrophobic part is obtained by modifying the outer surface of the shell layer with an alkyl-containing silane coupling agent; preferably, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

3. The magnetic multifunctional polymer-inorganic hybrid amphiphilic particles according to claim 1 or 2, characterized in that: The particle size of the magnetic multifunctional polymer inorganic hybrid amphiphilic particles is 100nm<r≤1000nm.

4. A method for preparing magnetic multifunctional polymer inorganic hybrid amphiphilic particles, characterized in that: include: S1. Dispersing magnetic Fe3O4 particles, tetraethyl orthosilicate and tetrabutyl titanate in an alcohol solvent to obtain Fe3O4@SiO2 / TiO2 particles; S2. Disperse Fe3O4@SiO2 / TiO2 particles in water, add paraffin, heat until the paraffin is completely melted, stir and mix, cool and filter, and obtain paraffin balls formed by Fe3O4@SiO2 / TiO2 particles embedded on the surface of paraffin; S3. dispersing the paraffin balls into dimethyl sulfoxide, adding an amino-containing silane coupling agent, stirring the reaction, and re-dispersing the obtained solid particles into an alcohol solvent to obtain hydrophilic modified particles; S4. The hydrophilic modified particles are dispersed in ethanol, an alkyl-containing silane coupling agent is added, and the reaction is stirred to obtain amphiphilic modified particles; S5. The amphiphilic modified particles are mixed with acetic acid for 8-12 hours to obtain core-shell separated amphiphilic modified particles; S6. The amphiphilic modified particles separated from the core-shell are dispersed in an alcohol solvent, 4-(chloromethyl)phenyltrimethoxysilane is added for modification reaction; and then grafted with diethylaminoethyl methacrylate to obtain grafted polydiethylaminoethyl methacrylate particles; S7. The particles grafted with polydiethylaminoethyl methacrylate are dispersed in a solvent, dopamine is added, and stirred for the first reaction; gallic acid is then added, and stirred for the second reaction. After the reaction is completed, the magnetic multi-functional polymer inorganic hybrid amphiphilic particles are obtained.

5. The preparation method according to claim 4, characterized in that: The stirring and mixing speed in step S2 is 1000-5000 rpm, and preferably, the stirring and mixing time in step S2 is 3-5 min; And / or, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane; And / or, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

6. The preparation method according to claim 4 or 5, characterized in that: The mass ratio of the magnetic Fe3O4 particles, tetraethyl orthosilicate and tetrabutyl titanate is 1:(0.1-1):(0.1-1); and / or, the mass ratio of the magnetic Fe3O4 particles to paraffin is 1:(10-200); And / or, the mass ratio of the magnetic Fe3O4 particles to the amino-containing silane coupling agent is 1:(0.001-0.01); And / or, the mass ratio of the magnetic Fe3O4 particles to the alkyl-containing silane coupling agent is 1:(0.001-0.01); and / or, the mass ratio of the magnetic Fe3O4 particles to 4-(chloromethyl)phenyltrimethoxysilane is 1:(0.001-0.01); and / or, the mass ratio of the magnetic Fe3O4 particles to diethylaminoethyl methacrylate is 1:(0.02-0.1); And / or, the mass ratio of the magnetic Fe3O4 particles to dopamine is 1:(0.001-0.01); And / or, the mass ratio of the magnetic Fe3O4 particles to gallic acid is 1:(0.001-0.01).

7. The preparation method according to any one of claims 4 to 6, characterized in that: The particle size of the magnetic Fe3O4 particles is 100 to 500 nm; And / or, the particle size ratio of the magnetic Fe3O4 particles and the magnetic Fe3O4 particle core is 100:(10-99).

8. The preparation method according to any one of claims 4 to 7, characterized in that: The grafting reaction comprises: dissolving cuprous chloride and 2,2-bipyridine in a solvent, adding amphiphilic modified particles treated by the modification reaction and diethylaminoethyl methacrylate, and stirring the reaction under a nitrogen atmosphere at 60-100° C.

9. A magnetic multifunctional polymer-inorganic hybrid amphiphilic particle prepared by the preparation method described in any one of claims 4 to 8.

10. Use of the magnetic multifunctional polymer-inorganic hybrid amphiphilic particles according to any one of claims 1 to 3 or the magnetic multifunctional polymer-inorganic hybrid amphiphilic particles according to claim 9 in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

Citation Information

Patent Citations

  • Application of poly-dopamine composite magnetic micro-nano particles in oily sewage treatment

    CN104098156A

  • Method for preparing silicon dioxide core-shell materials with core-shell spacing

    CN104961133A

  • A mesoporous magnetic polymer composite sphere, a preparing method thereof and applications of the composite sphere

    CN105435753A

  • Amphiphilic and magnetic nano-particles and preparation method thereof

    CN110211757A

  • PH-responsive composite Janus nanoparticles and preparation method thereof

    CN114644823A